A Case Study on Enhancing Student Learning Outcomes in Cost Estimation through Project-Based Learning at SMK Negeri 2 Payakumbuh - Ernisasneli (Journal of Hypermedia & Technology-Enhanced Learning, 2023)
This study aims to improve student learning outcomes in the subject of cost estimation through the implementation of the Project-Based Learning (PjBL) model. The research was conducted at SMK Negeri 2 Payakumbuh, with the participants being students of class XI TKJIJ. The method used is Classroom Action Research (CAR), conducted in two cycles, each involving planning, action, observation, and reflection. Each cycle was implemented to identify and evaluate student knowledge and skills improvement. The results show that the implementation of PjBL successfully enhanced students' understanding of cost estimation concepts, with the average learning outcomes increasing from 50.33 in the pre-cycle to 78.66 in Cycle II. The percentage of classical completeness also increased from 36.66% to 86.67% by the end of the cycle. Based on these findings, it can be concluded that the PjBL model is effective in improving student learning outcomes in vocational subjects, particularly in cost estimation. These findings are expected to contribute to improving the quality of education in vocational schools and can be applied to other practical subjects.